Totalitaryzm w historii kina science fiction - Patrzylas, Artur (In Gremium. Studies in History, Culture and Politics, 2016)
TOTALITARIANISM IN HISTORY OF SCIENCE FICTION FILM Science fiction genre has more than a hundred years of history. At this time, it has experienced a significant evolution, being divided into several subgenres along the way. The purpose of this article is to systematize, analyze and describe this extremely extensive genre, which is very important, both because of its artistic contribution to the history of cinema, as well as its content, including the characteristics of the population, eminent units and their types and exemplification. Science fiction cinema has also never avoided political references. The history of science fiction film has been introduced in chronological order. The timeframe of the analysis results from subjective and intuitive selection and the purpose of this is the fullest and most transparent presentation of the genre history. The article is about the whole science fiction, however, particular interest will be aimed at films referring to the issue of totalitarian regimes.